Systemic lupus erythematosus and vitamin D - N. G. Klyukvina (Современная ревматология)
The review presents the data available in the literature on the rate of hypovitaminosis D in systemic lupus erythematosus (SLE), analyzes the associations between the clinical and laboratory parameters of the disease and the levels of vitamin D, and considers the possibilities of the therapeutic use of its metabolites.Vitamin D deficiency is a very common pathological condition that creates prerequisites for the development of a wide range of diseases. The low serum level of vitamin D may be associated with insufficient solar exposure, genetic predisposition (vitamin D receptor polymorphism), and alimentary factors and may accompany autoimmune diseases. The very recently revealed immunomodulatory properties of vitamin D are of interest with respect to the possible implication of this hormone in the pathogenesis of autoimmune (including rheumatic) diseases. A number of investigators propose to regard vitamin D as a modifying environmental factor involved in the development of autoimmune diseases. There is evidence for the association of low serum 25(ОН)D levels with a risk for some rheumatic diseases (primarily rheumatoid arthritis and SLE), their activity, severity, and prognosis, which calls for further investigation. The antiresorptive, anti-inflammatory, and immunomodulatory effects of vitamin D metabolites substantiate that the latter should be used in combination with traditional disease-modifying agents to treatchronic inflammatory diseases.